Cardiovascular disease and nutrition: The use of food-based dietary guidelines for prevention in Africa - Pisa, P.T.; Vorster, H.H.; Nishida, C. (SA Heart Journal, 2017)
There is no doubt that morbidity and mortality from cardiovascular disease (CVD) are increasing in many African countries. Research and implementation of public health nutrition programmes in the developed world have shown that CVD can be prevented by dietary interventions. The objectives of this paper are to (i) review the relationships between diet and CVD; (ii) review the possible contribution of the nutrition transition, which is associated with economic development and “modernisation” to CVD in Africa; (iii) identify barriers and challenges plus assessing the opportunities available to steer the nutrition transition into a more positive direction; and (iv) show how ideal nutrient intakes can be translated into appropriate food based dietary guidelines (FBDGs) and how to apply these for prevention and management of CVDs. This should result in appropriate recommendations for diets that will be country-specific, affordable, culturally acceptable and based on available, traditional and indigenous foods. It is concluded that all health professionals should be sensitised, informed, trained and/or educated to apply FBDGs in a way that will motivate the public or patients to follow healthier diets for primary, secondary and tertiary prevention and treatment of CVD.